Quindici Anni 1991-2006 - Scuderie Aldobrandini (Museo Tuscolano - Auditorium - Sale Expositive), Frascati (Frascati Roma : Il Polittico - Associazione d'Arte e Cultura Roma Scuderie Aldobrandini (Museo Tuscolano - Auditorium - Sale Expositive) Frascati, 2006)
Abate, Alberto ; Acerbi, Rosetta ; Albert, Hermann ; Bartolini, Ubaldo ; Bellobono, Angelo ; Bergomi, Giuseppe ; Bertocci, Carlo ; Boldrini, Andrea ; Bonechi, Lorenzo ; Bulzatti, Aurelio ; Castillo, Juanjo ; Ceccotti, Sergio ; Corey, Thomas ; Cornini, Marco ; D'Ambrosio, Silvano ; dell'Aquila, Paolo ; demetz, aron ; Durini di Monza, Giulio ; Enrich, Ramon ; Escauriaza, Juan ; Fabbri, Angelo ; Fabrizi, Stefania ; Fani, Mario ; Fiorentino, Paolo ; Forns Bada, Carlos ; Frongia, Lino ; Gálvez, Alberto ; Gandolfi, Paola ; Henry, Sean ; Holland, Harry ; Zucchi, Fernando ; Ciroli, Eleonora ; Iglesias, Miguel Ángel ; Keen, Anna ; Kirby, John ; Knap, Jan ; Lazkano, Jesus Mari ; Ligare, David ; Livadiotti, Massimo ; Marci, Tito ; Marrone, Salvatore ; Martin Begué, Sigfrido ; McKenna, Stephen ; Mehrkens, Klaus Karl ; Mileto, Stefania ; Mingotti, Alberto ; Pearlstein, Philip ; Piccioni, Simone ; Piruca, Franco ; Pulvirenti, Salvatore ; Reggio, Mauro ; Ricci, Lithian ; Russo, Salvo ; Salvo, Lily ; Scarpella, Livio ; Schmidlin, Paolo ; Stasio, Stefano Di ; Stefanon, Gianni ; Tait, Renny ; Tirelli, Giuseppe ; Tonelli, Giorgio ; Valls, Dino ; Volpi, Angela ; Zoda, Giovanni
Publication on the occasion of the exhibition 'Quindici Anni 1991-2006' at the Scuderie Aldobrandini (Museo Tuscolano - Auditorium - Sale Expositive) in Frascati, 23.04.2006-04.06.2006
boek